MACRO HERD BEHAVIOUR AND THE SIZE EFFECT: A COMPARATIVE ANALYSIS BETWEEN SHARIA (ISSI) AND NON-SHARIA STOCKS IN INDONESIA - Laurensius Avellino; Vivi Liu; Kim Sung Suk (Program Studi Ekonomi Syariah, 2025)
This study aims to identify and analyze the patterns of macro herding behavior in the Indonesian Stock Market (IHSG) and to compare the intensity of general herding and the influence of Market Capitalization (Size Effect) between the Sharia Stock Index (ISSI) and Non-ISSI sub-samples. Utilizing weekly stock price data from all IDX-listed companies for the 2011???2024 period, the study applies the more robust Tessler and Venezia Herding Model (2022). Comparative analysis is performed on the Total IHSG, ISSI, and Non-ISSI segments. It is found that macro herding is detected in the IHSG, predominantly during extreme market conditions. The intensity of general herding is found to differ significantly between the ISSI and Non-ISSI groups, and the influence of Market Capitalization on herding also exhibits distinct patterns across the two sub-samples.The originality lies in the application of the robust Tessler and Venezia Model (2022) in the Indonesian Market and the comparative analysis of herding and Size Effect in the dualistic ISSI/Non-ISSI market. The findings confirm that Sharia compliance and firm size are important determinants moderating collective investor behavior, providing strong practical implications for regulators (OJK) and market participants.